Aspects of beach sand movement, at Gibraltar Point, Lincolnshire - Fox, Howard R. (1978)
In this study fluorescent sand tracer techniques were used to investigate sediment movement on the foreshore at two sites on the south Lincolnshire coast. Working over one tidal cycle, low water to low water tracer release at different points across the beach revealed a complexity of sand movement in this strongly tidal environment. It was found that sand moved both at different rates and in contrasting dominant directions on different parts of the beach over the same tidal cycle. At Gibraltar Point there was confirmation from the tracer experiments of the importance of tidal generated currents on sand movements on the lower foreshore.